Minimal invasive treatment for post‐liver and renal transplant lymphatic leaks. Issue 7 (16th May 2022) - Liu, Hsien‐Tzu; Liu, Chien‐An; Wang, Hsin‐Kai; Chen, Cheng‐Yen; Liu, Chin‐Su; Shen, Shu‐Huei
Abstract: Introduction: Persistent lymphatic leakage from the surgical drain is a troubling complication occasionally encountered postoperatively. This study investigated lymphatic leaks after renal or liver transplantation, comparing the treatment efficacy of traditional catheter drainage vs. minimally invasive lymphatic interventions. We also discuss access and treatment targets considering the physiology of lymphatic flow. Methods: Between September 2018 and September 2020, 13 patients with lymphatic leakage were treated with minimally invasive lymphatic interventions; 11 had received a renal transplant, and two received a liver transplant. The control group included 10 patients with postrenal transplant lymphatic leakage treated with catheter drainage. The treatment efficacy of catheter drainage, lymphatic interventions, and different targets of embolization were compared. Results: The technical success rate for lymphatic intervention was 100%, and the clinical success rate was 92%, with an 82.9% reduction in drain volume on the first day after treatment. The duration to reach clinical success was 5.9 days with lymphatic intervention, and 33.9 days with conservative catheter drainage. Conclusion: Lymphangiography and embolization are minimally invasive and efficient procedures for treating persistent lymphatic leaks after renal or liver transplantation. We suggest prompt diagnosis and embolization at upstream lymphatics to reduce the duration of drain retention, days of hospitalization, and associated comorbidities.